Pengaruh Kualitas Informasi, Kemudahan Penggunaan Dan Citra Perusahaan Terhadap Kepercayaan Nasabah Dan Dampaknya Pada Keputusan Penggunaan Bca Mobile (Studi Pada Mahasiswa Fakultas Ekonomika Dan Bisnis Universitas Stikubank Semarang) - Lailatu Zahro; Markus Surkamta Eric Santosa (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The original aim of this study was to find out the impact of issue qualiti, ease of use and company image on customer believes and their influence on the decision to use BCA mobile phones. The population of this study means mobile BCA users who are still active as Faculty students Economics and Business, University of Stikubank Semarang using a amount sample of 112 respondent. Information was collected by developing questionnaire. The analysis technique used in this study is linear regression analysis. Research results show that’s the quality of information has a positive influence on trust, ease of use has an positive effet on trus’t, corporate image has a positive effect’s on trust andd trust has positive efect ono usage preferences. Keywords : Company Image; Customer Trust; Decisions About The Use; Ease of Use; Information Quality